Helicopter Aircrew Cumulative Neck Loads from Integrated Task and Physical Demands Analyses. (September 2016) - Farrell, Philip S. E.; Tack, David W.; Nakaza, Edward T.; Bray-Miners, Jordan
Task and physical demands analyses together can identify common and extreme postures and postural sequences, duration, frequency, and forces for Griffon Helicopter aircrew tasks and missions. A tasks and associated physical demands model was developed to estimate neck loads caused primarily by Night Vision Goggle usage. This integrated task and physical demands analysis was used to assess various solutions such as counterbalance or lighter helmets.